Pengaruh Literasi Syariah, Green Orientation, Islamic Business Ethics, dan Inovasi Berkelanjutan terhadap Sustainability Performance UMKM Fashion di Yogyakarta - Nina Mudrikah Hariyati; R. Andro Zylio Nugraha (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This study aims to examine the effect of Islamic financial literacy, green orientation, Islamic business ethics, and sustainable innovation on the sustainability performance of fashion SMEs in Yogyakarta, Indonesia. This research adopts a quantitative approach using a survey method, with data collected from 200 fashion SME owners selected through purposive sampling. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that all proposed variables significantly influence sustainability performance. Sustainable innovation emerges as the most influential factor, followed by green orientation, Islamic business ethics, and Islamic financial literacy. These results indicate that the integration of sustainability-oriented practices and Islamic values plays a crucial role in enhancing the long-term performance of SMEs. From a theoretical perspective, this study contributes to the literature by integrating Resource-Based View and Dynamic Capabilities Theory in explaining sustainability performance within an Islamic context. Practically, the findings suggest that SME owners should strengthen their understanding of Islamic principles, adopt environmentally friendly practices, and foster innovation to achieve sustainable competitiveness. This study provides a novel framework by combining Islamic values and sustainability perspectives, particularly in the context of fashion SMEs in a developing country. Future research is recommended to incorporate moderating variables such as government support and digital capability to enrich the model.